PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE FORMULATE-SHARE-LISTEN-CREATE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMP N 15 PADANG - Putri, Niken Audri Rianda (Jurnal Edukasi dan Penelitian Matematika, 2023)
Mathematical communication is important aspect that must be achieved in mathematics learning. Based on the observations results at SMPN 15 Padang, it shows that the skills of communication in mathematical of class VIII students are still not optimal. Efforts to overcome this problem are in the shape of implementing the Formulate-Share-Listen-Create (FSLC) model. The research purpose was to find out whether the skills of communication in mathematical of students who studied using the FSLC cooperative model were better than students who learned using the direct learning model with direct. This research type is a quasi-experiment with the nonequivalent posttest-only control group design. The research population was class VIII students of SMPN 15 Padang for the 2022/2023 learning year. This research used technique by simple random sampling. The instrument for research was in the shape of a final test of mathematical communication skills. Based on the final test of the hypothesis test obtained p-value = 0.008, which means rejecting H0. Thus we got the conclussion that there is an influence on students' mathematical communication abilities after the FSLC model is applied.Keywords–  Formulate-Share-Listen-Create(FSLC), Mathematical Communication Skills